Two new species of Lepanthes (Orchidaceae: Pleurothallidinae) from Costa Rica and their phylogenetic affinity - Bogarín Chaves, Diego Gerardo (2020)
Lepanthes is one of the most species-rich genera of angiosperms in the neotropics. Here, we describe and illustrate two new species of Lepanthes from Caribbean lowlands of Costa Rica. Lepanthes crucitasensis, sp. nov. resembles L. confusa, from which it can be distinguished by longer and wider leaves and flowers with entire margin sepals, longer lateral sepals, longer upper lobe and lip with glabrous appendix. Lepanthes adenophora sp. nov. is similar to L. crucitasensis, but it is distinguished by the narrower leaves, always green, shorter inflorescences, pink scarlet petals with a yellow center and with the upper and lower lobe of different lengths, lip not surpassing the column, appendix with glandular trichomes and obovoid-elliptic pollinia. Micromorphologically, the petals of L. adenophora are pubescent or papillose–hispid. Both new species conform a clade closely related to two species from montane forests, suggesting that some lineages can potentially survive or adapt to warmer habitats. Our results demonstrate that alpha-taxonomic studies are pivotal for uncovering phylogenetic relationships in poorly sampled neotropical orchid groups.